Implication of satellite images in studying potential hydrocarbon resources in the licence Blocks 9 and 11, the exclusive economic zones of Egypt and Cyprus - O. M. Rusakov; I. N. Korchagin; N. A. Yakymchuk; S. P. Levashov; V. D. Soloviev; D. N. Bozhezha (Геофизический журнал, 2018)
A frequency-resonance technology was used for processing and decoding the satellite images of the licence Blocks 9 and 11 in the Eastern Mediterranean. The anomalies of “oil and gas” type were revealed in the study area. The supergiant Zohr gas field produces the prominent anomaly covering the largest area of 251 km2. This anomaly evidences for the channels for vertical migration of deep hydrocarbon-bearing fluids and the horizontal gradient in reservoir pressure. For the first time, these two specific findings were suggested to be indicators of a commercial discovery. Based on them, several “oil and gas” type anomalies were recommended for exploration drilling in the Blocks 9 and 11. Available information cannot allow us to consider the Onisiforos discovery as a commercial gas field. The siliciclastic and carbonate plays are equally workable in the Egyptian, Cypriot and Israeli EEZs where in the Miocene sediments abiogenic methane is the main component of gas which ascends to reservoirs from deeper layers. Selecting an optimal drilling location requires an interdisciplinary approach.